Cryoablation for the treatment of chronic rhinitis: a systematic review - Veeral Desai; Gianluca Sampieri; Amirpouyan Namavarian; John M. Lee (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background ClariFix is a novel intranasal cryotherapy device developed for clinic-based cryosurgical ablation of the posterior nasal nerves region. As a relatively new technology, there is a paucity of studies within the literature assessing the efficacy and safety profile of ClariFix for chronic rhinitis. Methods A systematic review was completed in accordance with PRISMA guidelines. Databases searched included: Ovid Medline, Ovid EMBASE, Pubmed, Cochrane and Web of Science. Inclusion criteria consisted of studies investigating the use of ClariFix in chronic rhinitis (i.e., allergic and non-allergic rhinitis) in patients of all ages. Results The initial search identified 1110 studies. Final analysis consisted of 8 articles, evaluating a total of 472 patients. The data showed a significant reduction in scores post-treatment across all studies based on validated outcome measures. In all studies, at all time intervals, there was a significant improvement in outcome scores from baseline. Minor adverse effects included post-procedural pain and discomfort, headache and palate numbness. No major adverse events were identified. Conclusion ClariFix is a novel intranasal cryotherapy device that was introduced in Canada in 2021. This is the first systematic review evaluating its efficacy and safety profile. Across all studies, there was a significant reduction in validated outcome scores at multiple time intervals. Further, the treatment is safe with only minor adverse effects reported by patients. Overall, the consensus from this study highlights an apparent benefit in using this intervention for chronic rhinitis that is refractory to medical management.